No association of serum PSA with vitamin D or total oxidant-antioxidant capacity in healthy men. (3rd July 2019) - Toprak, Burak; Colak, Ayfer; Yalcin, Hulya; Yildirim, Mustafa
Abstract: Background and aim: Vitamin D deficiency and oxidative stress were suggested to be related to prostate cancer risk. We aimed to investigate the association of serum PSA concentration with vitamin D and total oxidant/antioxidant levels. Materials and methods: A total of 95 healthy men were enrolled for the cross sectional study. Serum PSA, 25(OH)D, serum total oxidant status, and total antioxidant status were measured. Results: Serum PSA was significantly negatively correlated with serum total oxidant status ( r = −0.309, p = .003) but there was no significant correlation between PSA and 25(OH)D ( p = .383) or total antioxidant levels ( p = .233). After adjustment for age BMI and smoking status with multiple regression analysis, there was no significant association between serum PSA and total oxidant status. Conclusion: We find no evidence for an association between PSA and vitamin D levels or serum total oxidant/antioxidant levels.